Exploring Women’s Embodied Experiences of ‘The Gaze’ in a Mix-Gendered UK Gym - Amy Clark (Societies, 2017)
Feminist and gaze researchers have conducted ongoing discussions surrounding issues relating to the gaze and its impact on female experience. Women have the ‘to-be-looked-atness’ characteristic, with the gaze being directed at the female body, commonly by a male. To date, the focus of feminist research surrounding men looking at women and the analysis how women make sense of looks between women remains limited and scattered. Drawing upon ethnographic data obtained from a PhD research project, this paper delves into the embodied experiences of female exercisers within a UK ‘working-class’ gym. By exploring the women’s own accounts of their living, breathing and sensing bodies as they exercise, I attempt to understand how they make sense of this physical culture, their embodied selves as well as broader constructions of the gendered body. Utilising a feminist phenomenological approach, I explore the social-structural position of women in a patriarchal system of gender relations, whilst simultaneously acknowledging and analysing the structural, cultural and historical forces and location, upon individual lived body experiences and gendered embodiment. Discussion is provided on how women make sense and interpret specific ‘gazes’ encountered within the gym culture from both men and women.